2015
DOI: 10.1177/2325967115595802
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play After Soleus Muscle Injuries

Abstract: BackgroundSoleus muscle injuries are common in different sports disciplines. The time required for recovery is often difficult to predict, and reinjury is common. The length of recovery time might be influenced by different variables, such as the involved part of the muscle.HypothesisInjuries in the central aponeurosis have a worse prognosis than injuries of the lateral or medial aponeurosis as well as myofascial injuries.Study DesignCase series; Level of evidence, 4.MethodsA total of 61 high-level or professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 30 publications
(38 reference statements)
3
44
1
Order By: Relevance
“…Following CMSI, three of the four recovery milestones were delayed for soleus injuries compared to gastrocnemius injuries, albeit not significantly. The recovery time for soleus injuries in this study was similar to what has been reported previously; Pedret et al 14 reported an overall RTP time frame of 29.1 ± 18.8 days in a mixed cohort of athletes. Soleus injuries may require longer recovery time frames due to anatomical factors.…”
Section: Discussionsupporting
confidence: 89%
“…Following CMSI, three of the four recovery milestones were delayed for soleus injuries compared to gastrocnemius injuries, albeit not significantly. The recovery time for soleus injuries in this study was similar to what has been reported previously; Pedret et al 14 reported an overall RTP time frame of 29.1 ± 18.8 days in a mixed cohort of athletes. Soleus injuries may require longer recovery time frames due to anatomical factors.…”
Section: Discussionsupporting
confidence: 89%
“…No systematic reviews or RCTs were identified. Three studies (two case-series and one retrospective observational) were included with a total number of 825 subjects 82–84. Very low quality of evidence was observed for a multimodal treatment consisting of passive treatment modalities and progressive exercises, which led to an average treatment time of 9 days (range: not reported) in one study82 and a 1 year reinjury rate of 6.8% (95% CI not reported) in another study 84.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (two case-series and one retrospective observational) were included with a total number of 825 subjects 82–84. Very low quality of evidence was observed for a multimodal treatment consisting of passive treatment modalities and progressive exercises, which led to an average treatment time of 9 days (range: not reported) in one study82 and a 1 year reinjury rate of 6.8% (95% CI not reported) in another study 84. Furthermore, platelet-rich plasma and rehabilitation showed a large and significant effect versus rehabilitation alone (Hedges’ g =1.78, 95% CI 1.19 to 2.37) on return to previous sport activity (very low quality of evidence) 83…”
Section: Resultsmentioning
confidence: 99%
“…Pedret et al 22 evaluated the association of different typical locations of the soleus muscle tears and their recovery times, which showed wide variation. However, soleus central intramuscular tendon injuries had a significantly longer recovery time.…”
Section: Discussionmentioning
confidence: 99%